Manufacturing in Digital Industries : Prospects for Industry 4.0 - Davim, J. Paulo (De Gruyter, 2020)
Digital Industry can provide the framework for examining the challenges of future production technology. This book describes some of the various aspects that can, and may, influence future manufacturing. Computational intelligence techniques, cyber-physical systems, virtual and cloud-based manufacturing and man-machine interaction are studied and some of the most recent research completed by international experts in industry and academia is considered. Case studies provide practical solutions.
Keywords: Manufacturing processes.; elektronické knihy; electronic books